2010
DOI: 10.1093/annonc/mdp544
|View full text |Cite
|
Sign up to set email alerts
|

Nonpegylated liposomal doxorubicin (Myocet™) combination (R-COMP) chemotherapy in elderly patients with diffuse large B-cell lymphoma (DLBCL): results from the phase II EUR018 trial

Abstract: R-COMP is an effective regimen for the treatment of DLBCL in elderly patients, with an acceptable tolerability profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 27 publications
7
51
2
1
Order By: Relevance
“…As expected, the most frequent grade 3 to 4 AEs were neutropenia and febrile neutropenia, which occurred in 48% and 13% of patients, respectively. However, the observed rates of AEs with DA-POCH-R did not differ from those reported in other dose-adjusted regimens [14][15][16][17] and were substantially lower than AE rates observed in a series of doxorubicin-free protocols [31][32][33][34][35][36][37][38][39][40]42,44 specifically tailored for elderly patients with DLBCL (Table 6).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…As expected, the most frequent grade 3 to 4 AEs were neutropenia and febrile neutropenia, which occurred in 48% and 13% of patients, respectively. However, the observed rates of AEs with DA-POCH-R did not differ from those reported in other dose-adjusted regimens [14][15][16][17] and were substantially lower than AE rates observed in a series of doxorubicin-free protocols [31][32][33][34][35][36][37][38][39][40]42,44 specifically tailored for elderly patients with DLBCL (Table 6).…”
Section: Discussionmentioning
confidence: 75%
“…The rate of cardiac toxicity recorded in our study is also among the lowest recorded when compared with results of other trials investigating R-CHOP, or R-CHOP-like regimens, in elderly patients with DLBCL. 18,[30][31][32]44 In our study, multivariate analysis revealed that the need for chemotherapy dose reduction was the only predictive factor of poor outcome, independently of age. Back in the days of first-generation chemotherapeutic regimens, when in a Southwest Oncology group (SWOG) study CHOP chemotherapy was reduced by 50% in patients over 65 years of age, CR rates declined.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Cardiotoxicity was low and a promising response rate was observed in this setting patients. Another interesting study regarding the safety and the efficacy of the R-COMP combination was recently published (Luminari et al, 2010). Seventy-five elderly patients with diffuse large B-cell lymphoma (DLBCL) were studied.…”
Section: Non-pegylated Liposomal Doxorubicin In Non-hodgkin Lymphomamentioning
confidence: 99%